Мент поганый: [повести] / Николай Леонов - Леонов Николай Иванович (Серия "Черная кошка", 1995)
Экземпляры: ф.21 (2004) / Инвентарный номер: 47907 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Л 47 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44